Peningkatan Kompetensi Komputasi Teknik Melalui Pelatihan MATLAB Tingkat Lanjut Berbasis Project-Based Learning di SMK Yadika 12 Depok - Ayu Mika Sherila; Luh Krisnawati (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2026)
Background: This community service activity aims to enhance students' engineering computational competencies at SMK Yadika 12 in Depok through MATLAB training based on Project-Based Learning (PBL). The training focuses on applying MATLAB to data analysis, system modeling, and numerical computation in engineering fields. The program was conducted over two days and involved 38 twelfth-grade students from the Computer and Network Engineering and Telecommunications program. Method: The activity stages included needs analysis, hands-on MATLAB and Simulink training, mini-project mentoring, and evaluation through pre-test and post-test assessments. The training materials emphasized data analysis, system modeling, visualization, and the solution of simple engineering problems aligned with the students’ areas of expertise. Results: The average score increased from 65.53 on the pre-test to 88.95 on the post-test. Most participants also demonstrated improved ability to apply MATLAB to problem-based mini-projects. These findings suggest that project-based training provides an initial positive impact on students’ conceptual understanding and engineering computational skills. Conclusion: Further, more detailed evaluation and continued mentoring are recommended to sustain and further develop the training outcomes.